Evaluating the effects of climate change on tree species abundance and distribution in the Italian peninsula - Attorre, Fabio; Alfò, Marco; De Sanctis, Michele; Francesconi, Fabio; Valenti, Roberto; Vitale, Marcello; Bruno, Franco (Applied Vegetation Science, 2011)
Question: What is the effect of climate change on tree species abundance and distribution in the Italian peninsula? Location: Italian peninsula. Methods: Regression tree analysis, Random Forest, generalized additive model and geostatistical methods were compared to identify the best model for quantifying the effect of climate change on tree species distribution and abundance. Future potential species distribution, richness, local colonization, local extinction and species turnover were modelled according to two scenarios (A2 and B1) for 2050 and 2080. Results: Robust Random Forest proved to be the best statistical model to predict the potential distribution of tree species abundance. Climate change could lead to a shift in tree species distribution towards higher altitudes and a reduction of forest cover. Pinus sylvestris and Tilia cordata may be considered at risk of local extinction, while the other species could ﬁnd potential suitable areas at the cost of a rearrangement of forest community composition and increasing competition. Conclusions: Geographical and topographical regional characteristics can have a noticeable inﬂuence on the impact of predicted climate change on forest ecosystems within the Mediterranean basin. It would be highly beneﬁcial to create a standardized and harmonized European forest inventory in order to evaluate, at high resolution, the effect of climate change on forest ecosystems, identify regional differences and develop speciﬁc adaptive management strategies and plans.
Keywords: generalized additive model; geostatistical; geostatistical methods; italian peninsula; methods; random forest; regression tree analysis

Modelización de la producción de pastos herbáceos en una dehesa del centro peninsular - Benavides, R.; ROIG, S.; Ponce, R. Alonso; López-Carrasco, C. (PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes, 2010)
Modelling pasture production and dynamics is a key objective for agroforestry systems man- agement for economic and conservation purposes. However, this is a complex task due to the large number of influencing factors and the characteristic diversity and heterogeneity of this production. The objective of this work is to analyze and model the pasture production in a dehesa of Central Spain. The study site is located in the Dehesón del Encinar (Toledo) state, in a low density dehesa (17 trees/ha). A first geostatistical approximation is used with data from two contrasted sampling years: 2008 and 2009. Sampling data include zones under tree influence and pasture without any canopy cover. Geostatistical techniques and GIS result to be efficient tools for analyzing and predicting pas- ture production as well as for agroforestry systems management. Key
The following values have no corresponding Zotero field: periodical: PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes pub-location: Zamora
Keywords: agro- forestry systems; geostatistical; herbaceous pastures; Mediterranean pastures; tree-pasture interaction